The management of cooperative and work-integrated education for academic institutions of higher education in Thailand - Jaroensombut, Lertlak; Chuaboon, Wanchai; Sakolnakorn, Thongphon Promsaka Na; Luengalongkot, Pongsatean; Auiwong, Kanokwan; Boonkawin, Surakarn; Yekpiewpong, Sakda; Dhammasaccakarn, Wanchai; Saiyasopon, Sukhumvit; Pakittawichit, Thananchakorn; Chaiyapong, Akkakorn (Asian Journal of Education and Training, 2023)
The purpose of this article is to explain the process and benefits of, as well as the obstacles and keys to, the success of education management in the Cooperative and Work-Integrated Education Program (CWIE) in Thailand’s higher education system. This study employs secondary data, which we analyze using content and descriptive analysis. Data analysis showed that cooperative education courses are taught in a coproduced manner between higher education institutions and business establishments (public, private, and community) so that graduates are ready to enter the real world of work immediately, develop competencies that match the needs of the labor market, and prepare for future job positions. In addition, cooperative education encourages students to gain professional, self-development, and academic skills from the knowledge they receive. Cooperative education is an activity or operational process that includes an effective planning process and cooperation from all parties, including the business establishment, as well as quality cooperative education, including educational standards, curriculum teaching, supervision standards, student’s standards, and measurement and evaluation standards. However, problems arise in cooperative education; for example, students should receive job training, and advisors do not receive much support. For the development of cooperative education, academic institutions should create a digital platform specifically for the management of cooperative education.